Estrutura de mercado e efeito espaço-temporal da geração distribuída fotovoltaica na Paraíba - Maurício, Clarisse Freire Barboza (2024)
Solar energy, converted from solar radiation into electricity or heat, is a renewable and sustainable source. This dissertation analyzed the market structure and the spatio-temporal effect of photovoltaic distributed generation in Paraíba. More specifically, location, distribution and concentration of the installed power of this technology in the state, from 2014 to 2021. Data on the installed power of photovoltaic Distributed Generation (DG), in kilowatts (kW), obtained from the National Electric Energy Agency were used. (ANEEL). The methodologies addressed were the systematic literature review, concentration indicators, exploratory analysis of spatial data, the Markov spatial chain and Scan statistics. The main results highlight that, in the systematic literature review, there is a predominance of articles that address public policies for renewable energy, with an emphasis on spatial analysis, whereas the circular economy has emerged significantly only since 2020. In Brazil, the adoption of photovoltaic technology saw exponential growth from 2020 onwards, in 2021 it totaled 9,988 MW installed, an increase of 156% compared to 2015. In Paraíba it had an installed capacity of 74 MW (2021) distributed across 217 municipalities. For exploratory analysis of spatial data, an Alto-Alto cluster was formed in the semi-arid region of Paraíba. The Markov spatial chain inferred that the semi-arid municipalities had better performances compared to the others, due to the edaphoclimatic conditions and high installed power per capita. The spatio-temporal effect, observed by Scan statistics, showed conglomerates in the semi-arid and coastal region of Paraíba. It can be concluded that the development of this dissertation contributed to a better spatial understanding of photovoltaic DG in Paraíba.